UNIVERSAL COMPLEX OF PSYCHOPHYSIOLOGICAL TESTING - Mazakov, T. Zh.; Jomartova, Sh.A.; Wojcik, Waldemar; Ziyatbekova, G. Z.; Amirkhanov, B. S.; Zholmagambetova, B.R. (Academic Scientific Journal of Computer Science, 2020)
An experimental version of the system of psychological testing with fixation in real time of physiological parameters of the tested person has been developed. The Data of photoplethysmogram (PPG) and galvanic skin reaction (GSR) have been determined as sources of physiological data. The soft & hardware complex of psychophysiological testing allows in relation to each question of the test to capture and evaluate the psychophysiological state of the testing person, which provides additional information for the psychologist. For experimental tests two methods were chosen, the first one was the Buss-Durkee technique (BDHI), which allows to diagnose the aggressiveness of the individual, and the second was the method of assessing the neuropsychological stability. These tests are recommended for use in psychological selection for military service [1-2]. The tests are adapted to the Kazakh language and tested on cadets of military institutions and students of civil Universities in Almaty.